Linking financial performance and efficiency to sustainability in banking sector: a literature synthesis - Krisciukaityte, Karolina; Balezentis, Tomas; Streimikiene, Dalia (Journal of Business Economics and Management, 2023)
Efficiency generally translates to better financial performance and profitability and, thus, is often taken into account when analyzing activity of the banking sector. The sustainability approach adds social and environmental effects to the economic ones. Even though there have been studies on the different facets of the sustainable banking and its dimensions, it is important to discuss the integration of the sustainability concept with banking efficiency and financial performance measures. The objective of this research is to identify the prevailing indicators of sustainable banking in the presence of considerations on bank financial performance and efficiency. Such indicators can be used in multiple frameworks directed towards specific goals. Therefore, this paper also discusses the notions of the sustainable banking alongside the used methods used to handle the sustainability indicators. Thus, this paper presents the comprehensive review of sustainable banking linked to financial performance and efficiency, where indicators, and methods are analyzed in an integrated manner.